Endothelial Epas1 Deficiency Is Sufficient To Promote Parietal Epithelial Cell Activation and FSGS in Experimental Hypertension - Luque, Yosu; Lenoir, Olivia; Bonnin, Philippe; Hardy, Lise; Chipont, Anna; Placier, Sandrine; Vandermeersch, Sophie; Xu-Dubois, Yi-Chun; Robin, Blaise; Lazareth, Hélène; Souyri, Michèle; Guyonnet, Léa; et al. (Journal of the American Society of Nephrology, 2017)
FSGS, the most common primary glomerular disorder causing ESRD, is a complex disease that is only partially understood. Progressive sclerosis is a hallmark of FSGS, and genetic tracing studies have shown that parietal epithelial cells participate in the formation of sclerotic lesions. The loss of podocytes triggers a focal activation of parietal epithelial cells, which subsequently form cellular adhesions with the capillary tuft. However, in the absence of intrinsic podocyte alterations, the origin of the pathogenic signal that triggers parietal epithelial cell recruitment remains elusive. In this study, investigation of the role of the endothelial PAS domain-containing protein 1 (EPAS1), a regulatory subunit of the hypoxia-inducible factor complex, during angiotensin II-induced hypertensive nephropathy provided novel insights into FSGS pathogenesis in the absence of a primary podocyte abnormality. We infused angiotensin II into endothelial-selective knockout mice and their littermate controls. Although the groups presented with identical high BP, endothelial-specific gene deletion accentuated albuminuria with severe podocyte lesions and recruitment of pathogenic parietal glomerular epithelial cells. These lesions and dysfunction of the glomerular filtration barrier were associated with FSGS in endothelial -deficient mice only. These results indicate that endothelial EPAS1 has a global protective role during glomerular hypertensive injuries without influencing the hypertensive effect of angiotensin II. Furthermore, these findings provide proof of principle that endothelial-derived signaling can trigger FSGS and illustrate the potential importance of the EPAS1 endothelial transcription factor in secondary FSGS.